Cosmology - Weinberg, Steven, 1933- (New York : Oxford University Press, 2008)
A textbooks on modern cosmology that describes the historical development of cosmology and provides a comprehensive treatment of the underlying physics of cosmology, from the tools for measurements of the structure and evolution of the universe to the puzzles of dark matter and dark energy, including an assortment of problems.
Includes bibliographical references and indexes.
Adult
Keywords: Cosmology; Cosmology